Public Greenspace and Life Satisfaction in Urban Australia - Ambrey, Christopher; Fleming, Christopher (My University, 2013)
This paper examines the influence of public greenspace on the life satisfaction of residents of Australia’s capital cities. A positive relationship is found between the percentage of public greenspace in a resident’s local area and their self-reported life satisfaction, on average corresponding to an implicit willingness-to-pay of $1172 in annual household income for a 1 per cent (143 square metres) increase in public greenspace. Additional results suggest that the value of greenspace increases with population density and that lone parents and the less educated benefit to a greater extent from the provision of public greenspace than the general population. In all, these results support existing evidence that public greenspace is welfare enhancing for urban residents and adequate allowance should be made for its provision when planning urban areas.
Urban Studies
Keywords: Satisfaction -- Life; Lifestyle; Satisfaction; Life; Lifestyle